(untitled) (Andamios, Revista de Investigación Social, 2013)
Public Policy Studies enable the examination of the design, process and outcomes of public interventions by evaluating the context in which the interventions are implemented. However, the Public Policy Studies have been largely ignored by the evaluative studies of the international development cooperation projects. Based on these grounds, this paper presents a proposal for analyzing the management of development cooperation projects based on the field of Public Policy. The proposal is based on interdisciplinary perspective and seeks to analyze the organizations implementing development projects as well as their interaction in three phases of public policy (formulation, implementation and evaluation). The article concludes that the analysis of the public should be included in the evaluations of the development cooperation.